Associations between NT-proBNP and psychosocial factors in patients with chronic systolic heart failure - Müller-Tasch, Thomas; Krug, Katja; Peters-Klimm, Frank (Journal of psychosomatic research, 2021)
Objective - B-type natriuretic peptides (BNPs) and their biologically inactive N-terminal parts, namely, NT-proBNPs, are used for diagnostic and prognostic purposes in patients with chronic heart failure (CHF). Associations of BNPs and NT-proBNPs with emotional factors may exist. As depressive and anxious comorbidities and decreases in quality of life (QoL) are common in CHF patients, we explored the associations between NT-proBNP and depression, anxiety, and QoL in patients with CHF using cross-sectional and longitudinal analyses. - Methods - We used baseline and one-year follow-up NT-proBNP measurements and sociodemographic and clinical data from 180 patients with systolic CHF from a case management study. Depression was assessed with the Patient Health Questionnaire 9 (PHQ-9), anxiety was assessed with the Generalized Anxiety Disorder Scale 7 (GAD-7), and QoL was determined using the Short Form 36 (SF-36) health survey. - Results - Univariate correlation analyses showed significant negative associations between NT-proBNP and the scores of four out of eight QoL domains (range: r = −0.159 to −0.285, p = .042 to 0.001) of the SF-36 but not between NT-proBNP and depression and anxiety scores. In cross-sectional and longitudinal multivariate regression analyses, no significant associations between NT-proBNP and psychometric variables were found. - Conclusion - In patients with stable, chronic systolic heart failure, only weak relations between NT-proBNP and QoL exist, but no relations between NT-proBNP and depression and anxiety were found. These findings are placed in the current research context of this topic. Implications for future experimental studies are discussed.